2008
DOI: 10.1136/gut.2007.125526
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant extrathymic T cell receptor gene rearrangement in the small intestinal mucosa: a risk factor for coeliac disease?

Abstract: Background: Coeliac disease is a small intestine enteropathy caused by permanent intolerance to wheat gluten. Gluten intake by patients with coeliac disease provokes a strong reaction by intestinal intraepithelial lymphocytes (IELs), which normalises on a gluten-free diet. Aim: To investigate whether impaired extrathymic T cell maturation and/or secondary T cell receptor (TCR) gene recombination in IELs are features of coeliac disease which could contribute to the failure of establishing tolerance to gluten. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Cryosections were stained as previously described with the modification that 1% Triton-X100 was included in the blocking buffer [10]. The antibodies used were mouse anti-human IL-17A monoclonal antibody (mAb) (clone BL-168, IgG1; BioLegend, San Diego, CA) and mouse anti-human Foxp3 mAb (clone236A/E7, IgG1; Abcam, Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryosections were stained as previously described with the modification that 1% Triton-X100 was included in the blocking buffer [10]. The antibodies used were mouse anti-human IL-17A monoclonal antibody (mAb) (clone BL-168, IgG1; BioLegend, San Diego, CA) and mouse anti-human Foxp3 mAb (clone236A/E7, IgG1; Abcam, Cambridge, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Intraepithelial T lymphocytes, particularly CD8 + cells, are the major contributors of IFN-γ and IL-10 in biopsies collected from CD patients with active disease at diagnosis while the relative contribution from T cells in the LP increases in active CD caused by challenge with gluten after a symptom-free period on gluten-free diet [4], [9]. Furthermore, children with CD have impaired capacity for extrathymic T cell receptor (TCR) rearrangement suggesting that the failure to establish tolerance to gluten is at least partly due to reduced capacity to generate T cells locally in the small intestinal mucosa [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bas et al20 showed that patients with CD may fail to regulate T cell response to gluten because of an impaired capacity for extra-thymic T cell receptor gene rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…The CD4+ T cells play an important role in tissue injury [50] and in lamina propria predominates the phenotype Th1 with production of cytokines in response to gluten stimulation [51] . Researches [52] showed that patients with CD may fail to regulate T cell response to gluten because of an impaired capacity for extra-thymic T cell receptor gene rearrangement. Th1 cells are abundant in the LP and responsible for the maintenance of a suitable environment for antibody production at the duodenal mucosa and for the cytotoxic activity of IELs in untreated CD patients [53] .…”
Section: Function Of the Cellsmentioning
confidence: 99%